International Group Exhibitions-The Long Walk-Site Specific Installation_CLONE - Antoniou, Klitsa (My University, 2026)
The Long Walk, Site Specific Installation,Walking as a Question | International Walking EncountersOrganized by Visual March to Prespa, Fine and Applied Arts of the School of Fine Arts of the University of Western Macedonia (EETF/UOWM), and by Made of Walking (VI)Greece